Quantum dot composite particle, preparation method thereof and photoluminescent device containing quantum dot composite particle

By forming an antioxidant layer and covering an inorganic oxide layer on the surface of the quantum dot, the problem of quantum dots being sensitive to moisture, oxygen and heat is solved, and its stability and life of the photoluminescent device are significantly improved.

CN119592320AActive Publication Date: 2025-03-11NAJING TECHNOLOGY CORPORATION LIMITED

Patent Information

Application Number
CN202510137921.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-07
Publication Date
2025-03-11
Estimated Expiration
2045-02-07

AI Technical Summary

Technical Problem

Quantum dots are highly sensitive to moisture, oxygen and heat, resulting in insufficient luminescence stability and affecting the life of photoluminescent devices.

Method used

By forming an antioxidant layer on the surface of the quantum dot and covering the inorganic oxide layer, it blocks the damage of small molecules (such as water and oxygen) to the quantum dots and improves the stability of the quantum dots.

Benefits of technology

It significantly improves the stability and life of quantum dot composite particles and photoluminescent devices, reduces brightness attenuation, and improves the service life of the device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119592320A_ABST
    Figure CN119592320A_ABST
Patent Text Reader

Abstract

The invention provides a quantum dot composite particle, a preparation method thereof and a quantum dot photoluminescent device containing the quantum dot composite particle. The quantum dot composite particle comprises a quantum dot, an antioxidant layer coordinated on the surface of the quantum dot and an inorganic oxide layer coating the antioxidant layer, an antioxidant of the antioxidant layer has a coordination group coordinated with the surface of the quantum dot, and the thickness of the antioxidant layer is 1-10 nm. The inorganic oxide layer is used as a first protection means of the quantum dots to block water and oxygen invasion; and the antioxidant is modified on the surface of the quantum dot to form the antioxidant layer, so that the damage of small molecules penetrating through the inorganic oxide coating layer to the quantum dot is prevented, and the stability of the quantum dot is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the technical field of quantum dot composites, and in particular to a quantum dot composite particle and a preparation method thereof, and a photoluminescent device containing the same. Background Art

[0002] Quantum dots have optical properties such as fluorescence emission wavelength that covers the entire visible light region, large Stokes shift, narrow PL emission peak, and high luminous efficiency, making them the next generation mainstream material for preparing LED color display devices. However, due to the characteristics of quantum dots such as high sensitivity to moisture, oxygen and heat, their luminescence stability needs to be further improved. Summary of the invention

[0003] The purpose of the present disclosure is to provide a quantum dot composite particle and a preparation method thereof, a photoluminescent device containing the same, and to improve the lifespan of the quantum dot composite particle and the photoluminescent device.

[0004] According to the first aspect of the present disclosure, a quantum dot composite particle is provided, which includes quantum dots, an antioxidant layer coordinated to the surface of the quantum dots, and an inorganic oxide layer coating the antioxidant layer, wherein the antioxidant in the antioxidant layer has a coordination group coordinated to the surface of the quantum dots, and the thickness of the antioxidant layer is 1 to 10 nm.

[0005] Optionally, the thickness of the inorganic oxide layer is 2-40 nm; preferably, the quantum dot composite particles are 15 nm-100 nm.

[0006] Optionally, the antioxidant is selected from one or more of hindered phenols, hindered amines, phosphites, thioesters or thioethers; preferably, the material of the inorganic oxide layer includes one or more of TiO2, ZrO2, Al2O3, ZnO, ZnMgO or SnO2.

[0007] According to the second aspect of the present disclosure, a method for preparing any of the above-mentioned quantum dot composite particles is provided, wherein quantum dots having a first ligand are dispersed in an organic solvent and added to a container, a mixed solution of a long-chain silane ligand and an antioxidant is continuously added to the container, and at least a portion of the first ligand is replaced by the long-chain silane ligand and the antioxidant; one or two of ethanol, a silicon-containing ester compound and a metal alkoxide are continuously added to the container, an acid or a base is added as a catalyst, and the reaction is performed for a first time to obtain a product; the product is separated, purified and dried to obtain quantum dot composite particles; wherein the long-chain silane ligand has a coordination group, the long-chain silane ligand also includes a siloxane group and a hydroxyl group, and the number of C atoms in the main chain of the long-chain silane ligand is 8 to 30.

[0008] Optionally, the mass of the long-chain silane ligand is 5% to 50% of the mass of the quantum dots having the first ligand.

[0009] Optionally, the mass of the antioxidant is 0.1% to 20% of the mass of the quantum dots having the first ligand.

[0010] Optionally, the mass of the organic solvent is 1 to 500 times the mass of the quantum dots having the first ligand.

[0011] Optionally, the coordinating group is selected from thiol, hydroxyl, amino, carboxyl, phosphate or phosphite; preferably, the long-chain silane ligand is selected from silane-PEG-carboxylic acid, 8-mercapto-1-octanol, 11-mercapto-1-undecanol or diethylenetriaminepropylmethyldimethoxysilane.

[0012] Optionally, the acid or base is an organic or inorganic acid solution or base solution, preferably, the acid is a hydrochloric acid solution or an acetic acid solution, and the base is a sodium hydroxide solution or a tetramethylammonium hydroxide solution.

[0013] According to a third aspect of the present disclosure, a quantum dot photoluminescent device is provided, and the quantum dot photoluminescent device comprises any one of the above-mentioned quantum dot composite particles.

[0014] By adopting the above technical solution, the antioxidant is pre-modified on the surface of the quantum dots to form an antioxidant layer to prevent small molecules (such as water and oxygen) that pass through the inorganic oxide layer from damaging the quantum dots, further improving the stability of the quantum dots, and thus improving the stability of the quantum dot photoluminescent device. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] The drawings constituting part of the present application are used to provide a further understanding of the present disclosure. The exemplary embodiments of the present disclosure and their descriptions are used to explain the present disclosure and do not constitute an improper limitation on the present disclosure. In the drawings:

[0016] Figure 1 A schematic diagram of the structure of a quantum dot composite particle according to an embodiment of the present disclosure.

[0017] Figure 2 The present invention is a schematic diagram of a process for preparing quantum dot composite particles according to an embodiment of the present invention.

[0018] Figure 3 This is a transmission electron microscope (TEM) photograph of a quantum dot composite particle according to an embodiment of the present disclosure.

[0019] Figure 4 The figure is a curve diagram showing the change in brightness decay and aging time of quantum dot photoluminescent devices according to some embodiments of the present disclosure.

[0020] Figure numerals: 1, quantum dots; 2, antioxidant layer; 3, inorganic oxide layer; 4, long-chain silane ligand. DETAILED DESCRIPTION

[0021] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.

[0022] According to the first aspect of the present disclosure, a quantum dot composite particle is provided, which includes quantum dots, an antioxidant layer coordinated to the surface of the quantum dots, and an inorganic oxide layer coating the antioxidant layer, wherein the antioxidant in the antioxidant layer has a coordination group coordinated to the surface of the quantum dots, and the thickness of the antioxidant layer is 1 to 10 nm.

[0023] The inventors found that the inorganic oxide coating on the surface of quantum dots cannot completely block the water and oxygen of small molecules. The quantum dots will still be slowly etched over a long period of time, and the photochemical stability will decrease. In addition, due to the presence of the inorganic oxide coating, the compounded antioxidant cannot directly act on the surface of the quantum dots, and the effect is minimal. In the scheme of this application, the inorganic oxide layer serves as the first protection means for quantum dots to block the invasion of water and oxygen; the antioxidant is modified on the surface of the quantum dots to form an antioxidant layer to prevent small molecules that pass through the inorganic oxide coating from damaging the quantum dots, further improving the stability of the quantum dots.

[0024] In some embodiments, the thickness of the inorganic oxide layer is 2-40 nm. In some embodiments, the quantum dot composite particles are 15-100 nm. In some embodiments, the shape of the quantum dot composite particles is spherical (including quasi-spherical).

[0025] In some embodiments, the antioxidant is selected from one or more of hindered phenols, hindered amines, phosphites, thioesters, or thioethers.

[0026] In some embodiments, the material of the inorganic oxide layer includes one or more of TiO2, ZrO2, Al2O3, ZnO, ZnMgO, or SnO2.

[0027] In some embodiments, the quantum dot composite particles can be used to prepare polymer microspheres.

[0028] According to the second aspect of the present disclosure, a method for preparing any of the above-mentioned quantum dot composite particles is provided, wherein quantum dots having a first ligand are dispersed in an organic solvent and added to a container, a mixed solution of a long-chain silane ligand and an antioxidant is continuously added to the container, and at least a portion of the first ligand is replaced by the long-chain silane ligand and the antioxidant; one or two of ethanol, a silicon-containing ester compound and a metal alkoxide are continuously added to the container, an acid or a base is added as a catalyst, and the reaction is performed for a first time to obtain a product; the product is separated, purified and dried to obtain quantum dot composite particles; wherein the long-chain silane ligand has a coordination group, the long-chain silane ligand also includes a siloxane group and a hydroxyl group, and the number of C atoms in the main chain of the long-chain silane ligand is 8 to 30.

[0029] In some embodiments, the quantum dots having the first ligand are in a powder state, and preferably the first ligand is a carboxylic acid having less than or equal to 22 carbon atoms.

[0030] In some embodiments, more than 50% of the first ligand is replaced by the long-chain silane ligand and the antioxidant. In some embodiments, the pH of the reaction system is 4-12 and not equal to 7.

[0031] In some embodiments, the temperature of the ligand exchange step is selected from 0 to 90° C., preferably 25 to 35° C. In some embodiments, the temperature of the alcoholysis condensation reaction is selected from 0 to 50° C., preferably 25 to 35° C.

[0032] In some embodiments, after the product is obtained, a precipitant is added to the product system to precipitate the product, thereby facilitating further separation and purification.

[0033] In some embodiments, the mass of the long-chain silane ligand is 5% to 50%, preferably 10% to 30%, of the mass of the quantum dots having the first ligand.

[0034] In some embodiments, the weight of the antioxidant is 0.1% to 20%, preferably 2% to 10%, of the weight of the quantum dots having the first ligand.

[0035] In some embodiments, the mass of the organic solvent is 1 to 500 times, preferably 50 to 200 times, the mass of the quantum dots having the first ligand.

[0036] In some embodiments, the mass of ethanol is 100% to 1000% of the mass of the organic solvent.

[0037] In some embodiments, the coordination group of the long-chain silane ligand or antioxidant is selected from thiol, hydroxyl, amino or carboxyl or phosphate or phosphite groups.

[0038] In some embodiments, the long chain silane ligand is selected from silane-PEG-carboxylic acid, 8-mercapto-1-octanol, 11-mercapto-1-undecanol, diethylenetriaminopropylmethyldimethoxysilane.

[0039] The ester compound containing silicon is not limited as long as it can react to form an inorganic oxide layer. In some embodiments, the ester compound containing silicon is selected from tetrabutyl silicate, tetramethyl silicate, tetraethyl silicate or tetrapropyl silicate.

[0040] In some embodiments, the acid or base is an organic or inorganic acid solution or base solution, preferably, the acid is a hydrochloric acid solution or an acetic acid solution, and the base is a sodium hydroxide solution or a tetramethylammonium hydroxide solution.

[0041] According to a third aspect of the present disclosure, a quantum dot photoluminescent device is provided, the quantum dot photoluminescent device comprising any of the above-mentioned quantum dot composite particles. The quantum dot photoluminescent device has excellent stability in use.

[0042] In some embodiments, the quantum dot photoluminescent device comprises an LED chip and silica gel, wherein the quantum dot composite particles are dispersed in the silica gel. The size of the LED chip is not limited.

[0043] In some embodiments, the quantum dot photoluminescent device described above is used in a display device.

[0044] Hereinafter, the embodiments are described in more detail with reference to specific examples. However, they are illustrative examples of the present disclosure, and the present disclosure is not limited thereto.

[0045] Example 1

[0046] Take 1.5 g of quantum dot powder (the first ligand is oleate) and dissolve it in 100 g of toluene. Add 0.2 g of diethylenetriaminepropylmethyldimethoxysilane and 0.05 g of antioxidant 264 (containing hydroxyl coordination groups) at room temperature, mix and dissolve evenly, heat to 70 °C and continue stirring for 5 h. After the liquid is cooled, inject 250 mL of anhydrous ethanol and stir magnetically to obtain a uniform mixed solution A.

[0047] 30 mL of water and 4 mL of 25% to 28% sodium hydroxide aqueous solution were added to 30 mL of anhydrous ethanol, and the mixture was uniformly mixed to obtain a mixed solution B. Mixed solution B, 20 mL of tetrabutyl silicate and 6 mL of zirconium n-propoxide were injected into mixed solution A and stirred at room temperature for 24 h. The reaction product was centrifuged and washed three times with a mixed solution of toluene and ethanol, and then vacuum dried to obtain quantum dot composite particles 1. The TEM morphology of quantum dot composite particles 1 is shown in FIG. Figure 3 shown.

[0048] 70 parts by mass of thermosetting methyl-phenyl silicone resin, 20 ppm of platinum catalyst and 30 parts by mass of quantum dot composite particles 1 were weighed and uniformly mixed, and then placed in a vacuum stirring degassing machine, and vacuum stirred and degassed for 5 min to 10 min at an orbital speed of 600 rpm and a rotation speed of 500 rpm to obtain a mixed glue.

[0049] The mixed glue was poured into the packaging cavity of the 4014 LED bracket using a glue dispenser, and the LED bracket was placed in an oven and baked at 150 °C for 2 h for curing.

[0050] After curing, the quantum dot LED package was taken out and placed in an oven at 65°C and relative humidity RH95%, and then lit at 80 mA for aging. The chip was taken out at regular intervals and its optical performance was tested using an integrating sphere.

[0051] Generally, LED aging is measured by brightness decay, which basically corresponds to the decline in quantum dot efficiency. Taking the first test point as 100%, the brightness data measured after aging divided by the first test point is the brightness percentage.

[0052] Example 2

[0053] Take 2 g of quantum dot powder (the first ligand is oleate) and dissolve it in 120 g of n-octane. Add 0.5 g of 11-mercapto-1-undecanol and 0.05 g of antioxidant 168 (containing phosphite group) at 30 °C, mix and dissolve evenly, heat to 70 °C and continue stirring for 5 h. After the liquid is cooled, inject 350 mL of anhydrous ethanol and stir magnetically to obtain a uniform mixed solution A.

[0054] Add 30 mL of water and 6 mL of acetic acid solution to 30 mL of anhydrous ethanol, mix well to obtain mixed solution B; inject mixed solution B and 10 mL of aluminum isopropoxide and 12 mL of zirconium n-butoxide into mixed solution A, and stir at room temperature for 24 h. Centrifuge the reaction product, wash it three times with a mixed solution of toluene and ethanol, and vacuum dry it to obtain quantum dot composite particles 2.

[0055] Weigh 70 parts by mass of thermosetting methyl-phenyl silicone resin, 20 ppm of platinum catalyst and 30 parts by mass of quantum dot composite particles 2, mix them evenly, and place them in a vacuum stirring degassing machine. Degas them under vacuum stirring at an orbital speed of 600 rpm and a rotational speed of 500 rpm for 5 min to 10 min to obtain a mixed glue.

[0056] The mixed glue was poured into the packaging cavity of the 4014 LED bracket using a glue dispenser, and the LED bracket was placed in an oven and baked at 150 °C for 2 h for curing.

[0057] After curing, the quantum dot LED package was taken out and placed in an oven at 65°C and RH95%, and then lit at 80 mA for aging. The chip was taken out at regular intervals and its optical performance was tested using an integrating sphere.

[0058] Example 3

[0059] Take 1.8 g of quantum dot powder (the first ligand is oleate) and dissolve it in 90 g of cyclohexane. Add 0.4 g of 8-mercapto-1-octanol and 0.15 g of glutathione (an antioxidant containing a thiol coordination group) at room temperature, mix and dissolve evenly, raise the temperature to 70 °C and continue stirring for 5 h. After the liquid is cooled, inject 220 mL of anhydrous ethanol and stir magnetically to obtain a uniform mixed solution A.

[0060] 30 mL of water and 5 mL of 25% tetramethylammonium hydroxide aqueous solution were added to 30 mL of anhydrous ethanol, and the mixture was evenly mixed to obtain a mixed solution B. Mixed solution B, 5 mL of tetrabutyl silicate and 26 mL of tetrabutyl titanate were injected into mixed solution A, and stirred at room temperature for 24 h. The reaction product was centrifuged and washed three times with a mixed solution of toluene and ethanol, and then vacuum dried to obtain quantum dot composite particles 3.

[0061] 70 parts by mass of thermosetting methyl-phenyl silicone resin, 20 ppm of platinum catalyst and 30 parts by mass of quantum dot composite particles 3 were weighed and uniformly mixed, and then placed in a vacuum stirring degassing machine, and vacuum stirred and degassed for 5 min to 10 min at an orbital speed of 600 rpm and a rotation speed of 500 rpm to obtain a mixed glue.

[0062] The mixed glue was poured into the packaging cavity of the 4014 LED bracket using a glue dispenser, and the LED bracket was placed in an oven and baked at 150 °C for 2 h for curing.

[0063] After curing, the quantum dot LED package was taken out and placed in an oven at 65°C and RH95%, and then lit at 80 mA for aging. The chip was taken out at regular intervals and its optical performance was tested using an integrating sphere.

[0064] Example 4

[0065] Take 2.5 g of quantum dot powder (the first ligand is oleate) and dissolve it in 150 g of toluene. Add 0.7 g of silane-PEG-carboxylic acid and 0.12 g of antioxidant 2246 (containing hydroxyl coordination groups) at room temperature, mix and dissolve evenly, heat to 60 °C and continue stirring for 6 h. After the liquid is cooled, inject 270 mL of anhydrous ethanol and stir magnetically to obtain a uniform mixed solution A.

[0066] Add 40 mL of water and 3 mL of 0.1 mol·L -1The mixture was mixed with 31 mL of hydrochloric acid solution to obtain a mixed solution B. The mixed solution B and 31 mL of aluminum isopropoxide were injected into the mixed solution A and stirred at room temperature for 24 h. The reaction product was centrifuged and washed three times with a mixed solution of toluene and ethanol, and then vacuum dried to obtain quantum dot composite particles 4.

[0067] Weigh 70 parts by mass of thermosetting methyl-phenyl silicone resin, 20 ppm of platinum catalyst and 30 parts by mass of quantum dot composite particles 4, mix them evenly, and place them in a vacuum stirring degassing machine. Degassing is performed under vacuum stirring at an orbital speed of 600 rpm and a rotational speed of 500 rpm for 5 min to 10 min to obtain a mixed glue.

[0068] The mixed glue was poured into the packaging cavity of the 4014 LED bracket using a glue dispenser, and the LED bracket was placed in an oven and baked at 150 °C for 2 h for curing.

[0069] After curing, the quantum dot LED package was taken out and placed in an oven at 65°C and RH95%, and then lit at 80 mA for aging. The chip was taken out at regular intervals and its optical performance was tested using an integrating sphere.

[0070] Comparative Example 1

[0071] 1.5 g of quantum dot powder was dissolved in 100 g of toluene, 0.2 g of diethylenetriaminepropylmethyldimethoxysilane was added at room temperature, the mixture was mixed and dissolved evenly, the temperature was raised to 70 °C and stirred continuously for 5 h, 250 mL of anhydrous ethanol was injected into the liquid after cooling, and a uniform mixed solution A was obtained by magnetic stirring.

[0072] Add 30 mL of water and 4 mL of 25% to 28% sodium hydroxide ammonia water to 30 mL of anhydrous ethanol, mix well to obtain mixed solution B; inject mixed solution B, 20 mL of tetrabutyl silicate and 6 mL of zirconium n-propoxide into mixed solution A, and stir at room temperature for 24 h. Centrifuge the reaction product, wash it three times with a mixed solution of toluene and ethanol, and vacuum dry it to obtain quantum dot composite particles.

[0073] 70 parts by mass of thermosetting methyl-phenyl silicone resin, 20 ppm of platinum catalyst and 30 parts by mass of composite particles 5 were weighed and uniformly mixed, and then placed in a vacuum stirring degassing machine, and vacuum stirred and degassed for 5 min to 10 min at an orbital speed of 600 rpm and a rotation speed of 500 rpm to obtain a mixed glue.

[0074] The mixed glue was poured into the packaging cavity of the 4014 LED bracket using a glue dispenser, and the LED bracket was placed in an oven and baked at 150 °C for 2 h for curing.

[0075] After curing, the quantum dot LED package was taken out and placed in an oven at 65°C and RH95%, and then lit at 80 mA for aging. The chip was taken out at regular intervals and its optical performance was tested using an integrating sphere.

[0076] Comparative Example 2

[0077] Weigh 70 parts by mass of thermosetting methyl-phenyl silicone resin, 20 ppm of platinum catalyst and 30 parts by mass of quantum dot powder, mix them evenly and place them in a vacuum stirring degassing machine. Degas the mixture for 5 min to 10 min at an orbital speed of 600 rpm and an autorotational speed of 500 rpm to obtain a mixed glue.

[0078] The mixed glue was poured into the packaging cavity of the 4014 LED bracket using a glue dispenser, and the LED bracket was placed in an oven and baked at 150 °C for 2 h for curing.

[0079] After curing, the quantum dot LED package was taken out and placed in an oven at 65°C and RH95%, and then lit at 80 mA for aging. The chip was taken out at regular intervals and its optical performance was tested using an integrating sphere.

[0080] Depend on Figure 4 The test results show that the LED lamp prepared by the method of Example 1 has good stability. After aging for 1000 hours at 80 mA, the brightness decay is maintained within 4%. The brightness decay of the LED lamps prepared by the methods of Examples 2, 3, and 4 is maintained within 7% after aging for 1000 hours. The brightness decay of Comparative Example 1 (without antioxidant) is 17% after aging for 1008 hours.

[0081] The above description is only a preferred embodiment of the present disclosure and is not intended to limit the present disclosure. For those skilled in the art, the present disclosure may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present disclosure shall be included in the protection scope of the present disclosure.

Claims

1. A quantum dot composite particle, characterized in that: The quantum dot composite particles include quantum dots, an antioxidant layer coordinated on the surface of the quantum dots and an inorganic oxide layer covering the antioxidant layer. The antioxidant in the antioxidant layer has a coordination group coordinated with the surface of the quantum dots, and the thickness of the antioxidant layer is 1-10 nm.

2. The quantum dot composite particle according to claim 1, characterized in that: The thickness of the inorganic oxide layer is 2-40 nm; preferably, the thickness of the quantum dot composite particles is 15 nm-100 nm.

3. The quantum dot composite particle according to claim 1, characterized in that: The antioxidant is selected from one or more of hindered phenols, hindered amines, phosphites, thioesters or thioethers; preferably, the material of the inorganic oxide layer includes one or more of TiO2, ZrO2, Al2O3, ZnO, ZnMgO or SnO2.

4. A method for preparing quantum dot composite particles according to any one of claims 1 to 3, characterized in that: Dispersing quantum dots with a first ligand in an organic solvent and adding the solution to a container, adding a mixed solution of a long-chain silane ligand and an antioxidant to the container, and replacing at least a portion of the first ligand with the long-chain silane ligand and the antioxidant; adding one or two of ethanol, a silicon-containing ester compound and a metal alkoxide to the container, adding an acid or a base as a catalyst, reacting for a first time, and obtaining a product; The product is separated, purified and dried to obtain the quantum dot composite particles; wherein the long-chain silane ligand has a coordination group, the long-chain silane ligand also includes a siloxane group and a hydroxyl group, and the number of C atoms in the main chain of the long-chain silane ligand is 8 to 30.

5. The preparation method according to claim 4, characterized in that: The mass of the long-chain silane ligand is 5% to 50% of the mass of the quantum dots having the first ligand.

6. The preparation method according to claim 4, characterized in that: The mass of the antioxidant is 0.1% to 20% of the mass of the quantum dots having the first ligand.

7. The preparation method according to claim 4, characterized in that: The mass of the organic solvent is 1 to 500 times the mass of the quantum dots having the first ligand.

8. The preparation method according to claim 4, characterized in that: The coordinating group is selected from thiol, hydroxyl, amino, carboxyl, phosphate or phosphite; preferably, the long-chain silane ligand is selected from silane-PEG-carboxylic acid, 8-mercapto-1-octanol, 11-mercapto-1-undecanol or diethylenetriaminepropylmethyldimethoxysilane.

9. The preparation method according to claim 4, characterized in that: The acid or base is an organic or inorganic acid solution or base solution. Preferably, the acid is a hydrochloric acid solution or an acetic acid solution, and the base is a sodium hydroxide solution or a tetramethylammonium hydroxide solution.

10. A quantum dot photoluminescent device, characterized in that: The quantum dot photoluminescent device comprises the quantum dot composite particles according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • Quantum dot polymer compound and preparation method thereof

    CN111875896A

  • Quantum dot composite material and quantum dot light-emitting diode

    CN113122230A

  • Quantum dot composite particle, preparation method and application thereof

    CN117363340A

  • Quantum-dot diffusion plate, and preparation method therefor and application thereof

    EP4474151A1

  • Luminescent fine particle

    JP2003329686A

Cited By

  • Quantum dot-multi-component composite particle, quantum dot diffusion plate and preparation method

    CN121555178A

  • Quantum dot-multielement composite particle, quantum dot diffusion plate and preparation method

    CN121555178B